Relationship between feeding practices and morbidity pattern of children under two years of age in a community setting at Mymensingh (Community Based Medical Journal, 2018)
This descriptive cross-sectional study was performed in the department of Pediatrics, Mymensingh Medical College Hospital to assess the feeding practices and their relationship with the morbidity pattern of children under two years of age. For this study four hundred (400) children from eight different Upazilla Health Complexes (UHC) of Mymensingh district were enrolled and UHCs were selected randomly. Mothers with their children under two years of age who gave voluntary, informed, written consent were included and very sick children, motherless children, handicapped children were excluded from the study. Immediately after registration, detailed history was taken from child's mother using a preset questionnaire and clinical examination (anthropometry and bipedal edema) was done. Among them, 214 children (53.5%) were male and 186 children (47.5%) were female and M: F=1.2:1. Regarding morbidity pattern, 17.3% had acute respiratory tract infection (ARI), 12.7% had acute watery diarrhea (AWD), 2.2% had dysentery, and 9.5% children had more than one disease. In exclusive breast feeding (EBF), acute respiratory tract infection was 10.24% where as in partial breast feeding it was 23.24% and acute watery diarrhea in exclusive breast-fed baby was 6.6% but in partial breast-fed baby it was 17.29%. Morbidity were more in children who started complementary feeding with luta, barley, suji and cow's milk with suji than with khichuri and mixed family diet.CBMJ 2018 January: Vol. 07 No. 01 P: 10-15